Tingkat N Yeri Lansia Dengan Remathoid Artritis Yang Aktif Dan Tidak Aktif Melakukan Senam Lansia Di Desa Tanggul Kulon Kecamatan Tanggul Kabupaten Jember - Bhakti Wahyudiyanto; Sunyoto (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Gymnastics seniors is a series of regular motion tone and direction is done by yourself or a group that aims to improve the functional ability of exercise to achieve that goal. Number of patients with arthritis remathoid in the world today, has exceeded 355 million. The purpose of this study was to determine the level of arthritis pain remathoid elderly with active and inactive elderly Jember do gymnastics. The design study is a descriptive study. The population in this study as many as 81, the sample is divided into two active respondents doing exercise 23 and 58 are not active at the gym by using purposive sampling techniques. The collected data is processed by way of Editing, Coding, Sorting, Data Entry, Tabulating. The results meninjukkan majority of respondents who actively participates in gymnastics experience mild pain which is as many as 14 respondents (60.9%). And most of the respondents who did not actively follow the gymnastics experience severe pain as many as 38 respondents (65.5%). Gymnastics seniors can reduce the pain experienced by the elderly. The less active elderly doing exercise pain experienced by the elderly will increasingly elderly berat.pentingnya exercises to reduce pain remathoid elderly with arthritis should be applied with a charity such as the elderly do gymnastics program once a week.